MOLECULAR DOCKING AND DYNAMIC SIMULATION OF ASTRAGALIN REVEALS INHIBITORY POTENTIAL AGAINST PANCREATIC LIPASE - ALIAS, NORSYUHADA; GHAZALI, SITI NUR AKMAL; ABDUL HAMID, AZZMER AZZAR (International Journal of Allied Health Sciences, 2020)
Obesity has been classified as a disease that affects many people around the globe. The prevalence continues to rise each year, thus finding an effective and safe treatment as an anti-obesity drug is a major issue for researchers. At present, the only anti-obesity that gained approval for long-term treatment by the Food and Drug Administration (FDA) is orlistat. It acts by inhibiting pancreatic lipase activity. Unfortunately, it is a synthetic drug and comes with unpleasant side-effects. Hence, there is a need to search for pancreatic lipase inhibitor from natural resources. Several studies have revealed that flavonoids from Nelumbo nucifera leave extract showed pancreatic lipase-inhibitory activity. In this study, flavonoids from N. nucifera namely leucoanthocyadin, rutin and astragalin were chosen to undergo molecular docking analysis using AutoDock 4.2. Astragalin displayed the best affinity towards pancreatic lipase as compared to the other two flavonoids. Astragalin produced more hydrogen bonds and had lower free binding energy compared to orlistat. Moreover, astragalin formed a strong hydrogen bond with key amino acid Ser152 in the catalytic triad and showed good ligand recognition as it also had a strong hydrogen bond with His151, Phe215, and Arg256. Pancreatic lipase-astragalin complex underwent molecular dynamic (MD) simulation using GROMACS ver. 4. Docking simulation revealed that this complex was more stable compared to the pancreatic lipase-orlistat complex. This preliminary in silico result proposed that astragalin might act as an anti-obesity agent through pancreatic lipase inhibition action.